Napabucasin Reduces Cancer Stem Cell Characteristics in Hepatocellular Carcinoma - Li, Ya; Han, Qiuju; Zhao, Huajun; Guo, Quanjuan; Zhang, Jian (Frontiers in Pharmacology, 2020)
Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer. Cancer stem cells (CSCs) are a rare population with self-renewal and multipotent differentiation capacity, and reside among the more differentiated cancer cells. CSCs are associated with tumor recurrence, drug resistance and poor prognosis. The aim of this study was to determine the efficacy of napabucasin against HCC and elucidate the underlying molecular mechanisms. Napabucasin significantly decreased the viability of HCC cells in vitro by inducing apoptosis and cell cycle arrest. In addition, it suppressed CSC-related gene expression and spheroid formation in vitro, indicating depletion of CSCs. The anti-neoplastic effects of napabucasin was also evident in homograft tumor-bearing mouse models. Our findings provide the scientific basis of conducting clinical trials on napabucasin as a new therapeutic agent against HCC.